TINJAUAN MAHAR DALAM PERKAWINAN ADAT MASYARAKAT SUKU MELAYU PESISIR DI KECAMATAN PANTAI LUNCI KABUPATEN SUKAMARA - Fia Saputra; Achmadi; Sanawiah (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2026)
This study aims to explore the role of dowry in traditional marriage practices among the Coastal Malay community in Pantai Lunci, Sukamara District. Using a qualitative approach and empirical method, this research collected data through in-depth interviews and participatory observation in January 2026. Dowry, which is a requirement in traditional marriage, serves not only as a religious obligation but also as a symbol of social status and prestige in the community. The results show that the amount of dowry is influenced by the family's socio-economic factors and the educational status of the groom's family. Variations in dowry amounts were observed based on the groom's family education status, with families with higher education levels tending to offer higher dowries. The study also identified social inequality in access to traditional marriages influenced by economic and educational conditions. Some families prefer to give dowry in the form of cash, gold, or symbolic items, reflecting the symbolic value and cultural traditions that are still highly regarded in the community. This research contributes to the development of more inclusive customary policies that align with the current socio-economic conditions.